Biosynthesis of Poly(3-Hydroxybutyrate-co-3-Hydroxyvalerate) by Cupriavidus necator B-10646 from Mixtures of Oleic Acid and 3-Hydroxyvalerate Precursors - Natalia O. Zhila; Galina S. Kalacheva; Viktoriya V. Fokht; Svetlana S. Bubnova; Tatiana G. Volova (Журнал Сибирского федерального университета: Серия Биология, 2020)
Polyhydroxyalkanoates have attracted much attention as biodegradable alternative to petroleum-based synthetic plastics. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] copolymer is one of the best characterized PHA copolymers because of its high commercial potential. However, commercial use of PHAs has been limited by their high price. One approach to reducing the cost of PHA production is to use inexpensive carbon sources (fatty acids, plant oils, etc.). The aim of this work was to study synthesis of P(3HB-co-3HV) by the Cupriavidus necator B-10646 bacterium grown on oleic acid and different biochemical precursors of 3HV. Bacterial cells were grown for 72 h at 30°C and 200 rpm on an incubator shaker. Salts of propionic or valeric acids were used as precursors of 3HV. The content and the composition of the polymer were determined by gas chromatography of fatty acid methyl esters. Lipids and polymer were extracted from biomass using the method of Folch. The addition of potassium propionate and valerate did not inhibit bacterial growth and polymer synthesis, the cell concentration and polymer content reaching 9.3-9.5 g/L and 80-83%, respectively. The addition of potassium valerate or propionate led to the synthesis of (P(3HB-co-3HV)) copolymer containing 21.2 and 14.3 mol% of 3HV, respectively. The number average molecular weight (Mn) of the polymer synthesized by the bacterium on oleic acid alone was 220 kDa; the polydispersity of the polymer was 3.5. The polymer synthesized in the presence of potassium valerate and propionate was characterized by a lower Mn (156-178 kDa) and a higher polydispersity of the polymer (4.4-4.9). The main fatty acids (FA) of intracellular lipids were oleic (33.26% of the total FA) and palmitic acid (27.48% of the total FA). The addition of potassium propionate or valerate did not cause any significant changes in the composition of the FA of intracellular lipids of the strain studied. This study demonstrates the ability of C. necator B-10646 to synthesize P(3HB-co-3HV) from mixtures of oleic acid and 3HV precursors. The data obtained can be used to develop and implement an economically feasible process of the P(3HB-co-3HV) production